Glutamatergic lateral habenula neurons modulate consolidation of associative memories - Srivastava, Snigdha; Wang, I-Ching; Kochukov, Mikhail Y.; Swanson, Jessica L.; Costa-Mattioli, Mauro; Arenkiel, Benjamin R. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionDespite the rise in psychiatric disorders worldwide, the underlying brain circuits responsible for these devastating conditions remain elusive. The lateral habenula (LHb) has emerged as a key brain structure in depression studies due to its hyperactive state in both patients and animal models. While this aligns with known roles in driving aversive states and regulating serotonin release, it is still unclear how acute and transient activity changes in the LHb can influence higher order cognitive processes such as learning, memory, and behavioral adaptation. Given the importance of these processes to psychiatric conditions, understanding how LHb activity impacts cognitive function allows novel insights into the neurobiological mechanisms of disorders like depression.MethodsTowards this goal, we used chemogenetic activation to temporarily excite glutamatergic neurons in the mouse LHb and assessed impacts on associative memory.Results and DiscussionSurprisingly, we found that transient activation of LHb impaired long-term memory, without affecting anxiety or depression-like behaviors. Specifically, post-training activation of LHb glutamatergic neurons disrupted object recognition and reward-based associative long-term memory, while sparing fear associated long-term memory. The memory impairment was restricted to a critical temporal window post-training/conditioning that corresponded with the consolidation stage of long-term memory. Strikingly, pairing LHb glutamatergic neuronal activation with systemic ketamine administration rescued the long-term memory deficits, indicating that LHb glutamatergic neurons modulate consolidation of associative memories via a NMDA-mediated mechanism. Together, these findings support a novel role for LHb glutamatergic neuronal activity in the consolidation of associative long-term memories.